Monitoring of Field Patrolling Efforts, Vietnam: Insights from a Forest Station in Pu Hu Nature Reserve - Dong Le Khac; Ao Xuan Hoa; Luyen Nguyen Tai; Nha Thi Huynh Nguyen; Kuaanan Techato (My University, 2021)
Monitoring of Field Patrolling Efforts, Vietnam: Insights from a Forest Station in Pu Hu Nature Reserve
Keywords: Patrolling monitoring; Forest station; Pu Hu